Integral use of simulation, design of experiments and KANBAN to evaluate and improve the performance of a production line (2019)
This article is the product of research developed in a production line, where we wanted to observe how the Design of Experiments (DOE) and the Kanban interact fully with the Discrete Simulation in order to improve the performance of the production system. The above was achieved by showing how the DOE serves to identify the relevant factors in the production process, to then be incorporated as input parameters in the simulation, and also, through the implementation of the Kanban tool type "Trigger" the performance improvements presented in such production line were evidenced. Based on the above, two simulations were made: One without the use of the Lean tool and another with its implementation. In this way, the improvement in the performance of the production line could be observed when incorporating the Kanban. For example, the "Ironing" process, which had a utilization rate of 36%, increased to 60.39% with the use of Kanban, the same thing happened to the "Weaving" process, which increased its use to 61.77%. In this way, a way to improve the performance of a production line supported in the combination of these three tools is illustrated.